The LINC01929/miR-6875-5p/ADAMTS12 Axis in the ceRNA Network Regulates the Development of Advanced Bladder Cancer - Xiong, YuFeng; Pang, MingRui; Du, Yang; Yu, Xi; Yuan, JingPing; Liu, Wen; Wang, Lei; Liu, XiuHeng (Frontiers in Oncology, 2022)
Considering its speedy development and extremely low 5-year overall survival rate worldwide, bladder cancer (BCa) is one of the most common and highly malignant tumors. Increasing evidence suggests that protein-coding mRNAs and non-coding RNAs, including long non-coding RNAs (lncRNAs) and micro RNAs (miRNAs), play an essential role in regulating the biological processes of cancer. To investigate the molecular regulation associated with poor prognosis during advanced BCa development, we constructed a competitive endogenous RNA (ceRNA) network. Using transcriptome profiles from The Cancer Genome Atlas and Gene Expression Omnibus databases, we performed differential expression (DE) analysis, weighted gene co-expression network analysis, functional enrichment analysis, survival analysis, prediction of miRNA targeting, and Pearson correlation analysis. Through layers of selection, 8 lncRNAs-28 mRNAs and 8 miRNAs-28 mRNAs pairs shared similar expression patterns, constituting a core ceRNA regulatory network related to the invasion, progression, and metastasis of advanced clinical stage (ACS) BCa. Subsequently, we conducted real time qPCR, western blotting, and immunohistochemistry to validate expression trend bioinformatics analysis on 3, 2, and 3 differentially expressed mRNAs, lncRNAs, and miRNAs, respectively. The most significantly differentially expressed LIN01919, miR-6875-5p and ADAMTS12 were selected for in vitro experiments to assess the functional role of the LIN01919/miR-6875-5p/ADAMTS12 axis. RNA pull-down, luciferase assays, and rescue assays were performed to examine the binding of LIN01919 and miR-6875-5p. Increasing trends in COL6A1, CDH11, ADAMTS12, LINC01705, and LINC01929 expression variation were verified as consistent with previous DE analysis results in ACS-BCa, compared with low clinical stage (LCS) BCa. Through experimental validation, the cancer-promoting molecule ADAMST12 was found to play a key role in the development of advanced BCa. Functionally, ADAMTS12 knockdown inhibited the progression of bladder cancer. Overexpression of LINC01929 promoted bladder cancer development, while overexpression of miR-6785-5p inhibited bladder cancer development. Mechanistically, LINC01929 acted as a sponge for miR-6785-5p and partially reversed the role of miR-6785-5p. Our findings provide an elucidation of the molecular mechanism by which advanced bladder cancer highly expressed LINC01929 upregulates ADAMTS12 expression through competitive adsorption of miR-6875-5p. It provides a new target for the prognosis and diagnosis of advanced bladder cancer.